Investigating the Correlation between Risk Assessment Results with Performance Indicators of Accidents in a Container Terminal - Fatemeh FASIH RAMANDI (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Knowledge of the relationship between risk levels and occurrence of events is one of the important elements in the development and implementation of programs to prevent the occurrence of accidents. The aim of this study was to assess the risk of jobs in container operations, and investigating the correlation of its results with accidents performance indicators. Methods: This cross sectional and descriptive-analytical study was carried out in one of container terminals in southern of Iran in 2016 - 2017. Failure Mode and Effects Analysis (FMEA) were used for risk identification and assessment. Accident Frequency Rate (AFR), Accident Severity Rate (ASR) and Frequency-Severity Index (FSI), were calculated. Data analysis was performed using the SPSS version 18 software.  Results: According to the results, 2, 56.19 and 24.8 percent of identified risks were reported as acceptable, tolerable, and intolerable, respectively. The mean of Risk Priority Number (RPN), AFR, ASR and FSI were equal to 171.26, 68.6, 400.1, and 1.84, respectively. Statistical significant relation was found between RPN, AFR, ASR, and FSI, as according to linear regression model for one unit increase in the RPN, the FSI, ASR, and AFR, the intensity has increased 0/064, 3.08 and 1.15 units, respectively. Conclusions: High levels of accident indicators and intolerable risks, as well as a significant relationship between the results of risk assessment and accident indicators, indicate weakness of the safety system in container operations. Therefore, the establishment of an effective safety system is necessary to improve safety and eliminate its noncompliances.